2015
DOI: 10.1056/nejmoa1503153
|View full text |Cite
|
Sign up to set email alerts
|

Daclatasvir plus Sofosbuvir for HCV in Patients Coinfected with HIV-1

Abstract: Among previously untreated HIV-HCV coinfected patients receiving daclatasvir plus sofosbuvir for HCV infection, the rate of sustained virologic response across all genotypes was 97.0% after 12 weeks of treatment and 76.0% after 8 weeks. (Funded by Bristol-Myers Squibb; ALLY-2 ClinicalTrials.gov number, NCT02032888.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
289
3
13

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 386 publications
(328 citation statements)
references
References 32 publications
23
289
3
13
Order By: Relevance
“…However, its interactions with specific ART drugs and regimens are being studied and dose modification recommendations are being finalized. 23 Table 1 highlights drug-drug interactions between DAA and some commonly prescribed medications. The University of Liverpool website, www.…”
Section: Daclatasvir (Dcv)mentioning
confidence: 99%
See 2 more Smart Citations
“…However, its interactions with specific ART drugs and regimens are being studied and dose modification recommendations are being finalized. 23 Table 1 highlights drug-drug interactions between DAA and some commonly prescribed medications. The University of Liverpool website, www.…”
Section: Daclatasvir (Dcv)mentioning
confidence: 99%
“…23,54 While SOF/RBV therapy has excellent efficacy in HCV GT-2, many patients may not be able to tolerate RBV. These patients may benefit from combination therapy with DCV and SOF.…”
Section: Genotypementioning
confidence: 99%
See 1 more Smart Citation
“…This decline will be further accelerated by the recent impressive improvement of efficacy of treatments for HCV chronic infection. Recent trials have shown that the current available interferon-free therapeutic regimens with the new direct-acting antiviral agents (DAAs) reach the sustained virological response in more than 90% of patients with cirrhosis, either naïve, relapsers or null responders to Interferon-based regimes, both HCV-monoinfected [30][31][32][33] and HCV/HIV coinfected [34][35][36]. A further impressive reduction of HCV-related mortality rate for liver cirrhosis is expected by a larger use of second and third generation DAAs.…”
Section: Discussionmentioning
confidence: 99%
“…The recommendation is based on the ALLY-2 trial which assessed the efficacy and safety of daclatasvir and sofosbuvir for 12 weeks in HIV and HCV co-infected patients [18]. SVR rate was 96% in treatment naive patients and 82% in treatment-experienced patients.…”
Section: Genotypementioning
confidence: 99%